2014
DOI: 10.1016/j.matbio.2014.01.003
|View full text |Cite
|
Sign up to set email alerts
|

A decorin-deficient matrix affects skin chondroitin/dermatan sulfate levels and keratinocyte function

Abstract: Decorin is a small leucine-rich proteoglycan harboring a single glycosaminoglycan chain, which, in skin, is mainly composed of dermatan sulfate (DS). Mutant mice with targeted disruption of the decorin gene (Dcn−/−) exhibit an abnormal collagen architecture in the dermis and reduced tensile strength, collectively leading to a skin fragility phenotype. Notably, Ehlers-Danlos patients with mutations in enzymes involved in the biosynthesis of DS display a similar phenotype, and recent studies indicate that DS is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 62 publications
(140 reference statements)
2
33
0
Order By: Relevance
“…We previously demonstrated that the reduced amount of Ust and the lack of 2-O sulfated CS/DS in skin or fibroblasts of Dcn 2/2 mice leads to an altered Fgf7-and Fgf2-binding capacity (Nikolovska et al, 2014), suggesting they have a new and important role in modulating the growth factor response. In the present study, we show that the degree of 2-O sulfation of cell surface CS/DS can modulate Fgf2-induced migration through ERK1/2 activation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously demonstrated that the reduced amount of Ust and the lack of 2-O sulfated CS/DS in skin or fibroblasts of Dcn 2/2 mice leads to an altered Fgf7-and Fgf2-binding capacity (Nikolovska et al, 2014), suggesting they have a new and important role in modulating the growth factor response. In the present study, we show that the degree of 2-O sulfation of cell surface CS/DS can modulate Fgf2-induced migration through ERK1/2 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the small non-coding microRNA149 has been linked to a new fine-tuning element of Fgf2-induced proliferation in endothelial cells by regulating the HS proteoglycan glypican (Chamorro-Jorganes et al, 2014). We have previously shown that the lack of decorin in skin led to the reduction of Ust and an impaired cell morphology in a 3D environment (Nikolovska et al, 2014;Jungmann et al, 2012), which could partially contribute to the delayed wound healing of the Dcn 2/2 mice (Järveläinen et al, 2006). We proved the importance of 2-O sulfation by showing that there was an impaired migration of 3T3 cells with a knockdown of Ust.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations